Sistema informático para automatizar la información académica, de investigación, vinculación y laboratorios de la Facultad de Ciencias de la Ingeniería y Aplicadas de la UTC empleando técnicas de data analytics - Banda Llanganate, David Alexander (2022)
The objective of this project is the development and implementation of a web system for the departments of Research, Liaison, and Laboratories at the Technical University of Cotopaxi for the Faculty of Engineering and Applied Sciences CIYA, which leads to delivering a product that meets the expectations of the Dean of the Faculty, Mauro Albarracín. The project's development has been executed under the adaptation of the agile Kanban methodology, where the application of research techniques such as interviews and surveys has also been implemented using as the only instrument a questionnaire for the survey. The Technical University of Cotopaxi has different areas already mentioned, where it has information of great relevance for its students and teachers, so the software development is for the benefit of teachers and students of the CIYA Faculty, the improvement, and automation in the delivery and management of academic information, research, liaison, and laboratories. For the development of the software, we used free software such as the CodeIgniter development framework and Bootstrap, and the main programming language is PHP. However, the use of technologies such as JavaScript and Ajax was added. The database was worked in PostgreSQL, and for the deployment, an Amazon Web Services AWS server was used as the host. In addition, GitLab was used for version management, and Trello was used for the Kanban board.